N‐glycosylation status of β‐haptoglobin in sera of patients with colon cancer, chronic inflammatory diseases and normal subjects - Park, Seung‐Yeol; Yoon, Seon‐Joo; Jeong, Yeon‐Tae; Kim, Jin‐Man; Kim, Ji‐Yeon; Bernert, Bradford; Ullman, Thomas; Itzkowitz, Steven H.; Kim, Jung‐Hoe; Hakomori, Sen‐itiroh (International journal of cancer, 2010)
N‐glycosylation status of purified β‐haptoglobin from sera of 17 patients, and from sera of 14 healthy volunteer subjects, was compared by blotting with various lectins and antibodies. Patients in this study were diagnosed as having colon cancer through histological examination of each tumor tissue by biopsy. Blotting index of serum β‐haptoglobin with Aleuria aurantia lectin (AAL) was clearly higher for cancer patients than for healthy subjects. No such distinction was observed for blotting with three other lectins and two monoclonal antibodies. To determine tumor‐associated reactivity of AAL binding as compared to inflammatory processes in colonic tissues, β‐haptoglobin separated from sera of 5 patients with Crohn's disease (CD), and 4 patients with ulcerative colitis (UC), was studied. All these cases, except one case of UC, showed AAL index lower than that in cancer cases, similarly to healthy subjects. The higher AAL binding of β‐haptoglobin in colon cancer patients than in healthy subjects appeared to be due to α‐L‐fucosyl residue, since it was eliminated by bovine kidney α‐fucosidase treatment. N‐linked glycans of serum haptoglobin from colon cancer patients vs. healthy subjects were released by N‐glycanase, fluorescence‐labeled, and subjected to normal‐phase high performance liquid chromatography (NP‐HPLC). Glycan structures were determined based on glucose unit (GU) values and their changes upon sequential treatment with various exoglycosidases. Glycosyl sequences and their branching status of glycans from 14 cases of serum β‐haptoglobin were characterized. The identified glycans were sialylated or nonsialylated, bi‐antennary or tri‐antennary structures, with or without terminal fucosylation.